DESAIN MEDIA PEMBELAJARAN ICT BERBASIS PEDAGOGI HIJAU UNTUK MAHASISWA CALON GURU BIOLOGI FKIP UNIVERSITAS RIAU - Sayyidatina, Anisah Sayyidatina; ', Firdaus LN; ', Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Has conducted research for the development of media design Information, Communication and Technology (ICT) -based Green Pedagogy for student teachers of biology FKIP University of Riau. This study was conducted from January to June 2015. This type of research is a kind of research development (Research and Development), the procedural ADDIE development model. ADDIE development procedures are implemented, namely Analysis, Design, Development and the trial was limited. The results showed that the validation of ICT-based Learning Media Pedagogy Green to KD 1.1 to KD 1.4 total mean value validation is 3,29 (valid). For Web-based validation Pedagogy Green to KD 1.1 to KD 1.4 total mean value validation is 3,24 (valid). Based on the results of research conducted, it can be concluded that the Learning Media Green ICT-based pedagogy that has been developed as a supplement to the subject Environmental Education and alternative courses in Prodi. UR Biology category is valid and can be implemented in the learning process. Key words: Design, Media learning ICT, Pedagogy Green